The Iranian version of the Copenhagen Psychosocial Questionnaire (COPSOQ) for assessment of psychological risk factors at work - Mohammad Aminian; Iman Dianat; Anvar Miri; Mohammad Asghari-Jafarabadi (Tabriz University of Medical Sciences, 2017)
Background: The Copenhagen Psychosocial Questionnaire (COPSOQ) is a widely used tool for evaluation of psychosocial risk factors at work. The aims of this study were to describe the short version of Farsi COPSOQ and to present its psychometric properties. Methods: A total of 427 administrative health care staff participated in this descriptive methodological study. Forward-backward procedure was adopted to translate the questionnaire from English into Farsi. Content validity was assessed by a panel of 10 experts. Construct validity was evaluated by exploratory and confirmatory factor analyses. The internal consistency and test-retest reliability were assessed using Cronbach's α and intraclass correlation coefficient(ICC), respectively. The feasibility was assessed using ceiling and floor effect. Results: The short version of Farsi COPSOQ was configured with 16 dimensions (32 items).Content validity of the questionnaire was established. Factor analysis supported the conceptualmulti-dimensionality (four factors), and therefore confirmed the construct validity of the Farsi COPSOQ. The internal consistency (Cronbach's α ranging between 0.75 and 0.89) and test retest reliability (ICC values ranged from 0.75 to 0.89) were both approved and the results showed no ceiling or floor effect. Conclusion: The results support the use of Farsi COPSOQ for evaluation of psychological risks and for research purposes in Iranian population.